Macroprudential policy – closing the financial stability gap. Issue 4 (13th November 2017) - Fahr, Stephan; Fell, John
Abstract : Purpose: The global financial crisis demonstrated that monetary policy alone cannot ensure both price and financial stability. According to theTinbergen (1952) rule, there was a gap in the policymakers' toolkit for safeguarding financial stability, as the number of available policy instruments was insufficient relative to the number of policy objectives. That gap is now being closed through the creation of new macroprudential policy instruments. Both monetary policy and macroprudential policy have the capacity to influence both price and financial stability objectives. This paper develops a framework for determining how best to assign instruments to objectives. Design/methodology/approach: Using a simplified New-Keynesian model, the authors examine two sets of policy trade-offs, the first concerning the relative effectiveness of monetary and macroprudential policy instruments in achieving price and financial stability objectives and the second concerning trade-offs between macroprudential policy instruments themselves. Findings: This model shows that regardless of whether the objective is to enhance financial system resilience or to moderate the financial cycle, macroprudential policies are more effective than monetary policy. Likewise, monetary policy is more effective than macroprudential policy in achieving price stability. According to theMundell (1962) principle of effective market classification, this implies that macroprudential policy instruments should be paired with financial stability objectives, and monetary policy instruments should be paired with the price stability objective. The authors also find a trade-off between the two sets of macroprudential policy instruments, which indicates that failure to moderate the financial cycle would require greater financial system resilience. Originality/value: The main contribution of the paper is to establish – with the help of a model framework – the relative effectiveness of monetary and macroprudential policies in achieving price and financial stability objectives. By so doing, it provides a rationale for macroprudential policy and it shows how macroprudential policy can unburden monetary policy in leaning against the wind of financial imbalances.